Confessional Component of Urbanonymy in Lexicographic Interpretation - T. G. Nikitina; E. I. Rogaleva (Научный диалог)
This article addresses the issues of enhancing the lexicographic representation of confessionally marked urbanonyms. The objective of the study is to substantiate parametric models for dictionary entries that allow for a comprehensive presentation of the confessional component of urbanonymy in both culturalhistorical and functional aspects. The research material is drawn from the database of the Experimental Laboratory of Educational Lexicography at Pskov State University, which contains 3,000 urbanonyms, including more than 200 ecclesionims (official, colloquial, and slang), forming the core of the urbanonymconfessionalism dataset. Through structuralsemantic and contextual analysis, the study identifies the denotative correlations, lexical composition of these urbanonyms, and various types of their variations in contemporary speech. Historical-etymological analysis aids in uncovering the motivations behind nomination. The method of linguocultural interpretation is employed in developing the commentary section of the dictionary entry. Lexicographic construction techniques are utilized in creating an improved model for entries in a general alphabetical urbanonym dictionary and an innovative discourse-type entry for an urbanonym guide dictionary. Samples of dictionary entries with accompanying comments are presented.